Constructing Ternary CdS–Graphene–TiO2 Hybrids on the Flatland of Graphene Oxide with Enhanced Visible-Light Photoactivity for Selective Transformation - Zhang, Nan; Zhang, Yanhui; Pan, Xiaoyang; Yang, Min-Quan; Xu, Yi-Jun (Journal of physical chemistry. C, 2012)
The ternary CdS–graphene–TiO2 hybrids (CdS–GR–TiO2) have been prepared through an in situ strategy on the flatland of graphene oxide (GO). The structure and properties have been characterized by a series of techniques, including X-ray diffraction (XRD), field-emission scanning electron microscopy (FE-SEM), transmission scanning electron microscopy (TEM), energy-dispersive X-ray spectroscopy (EDX), UV–vis diffuse reflectance spectra (DRS), electrochemical analysis, photoluminescence spectra (PL), nitrogen adsorption–desorption, and electron spin resonance spectra (ESR). Combined with our previous results, it is found that the introduction of the third-component TiO2 can maintain the morphology and porosity of the samples, whereas it is able to tune the energy band, increase the surface area, and facilitate the electron transfer, thus prolonging the lifetime of photogenerated carriers. Taking photocatalytic selective oxidation of various alcohols to their corresponding aldehydes as model reactions, the ternary CdS–GR–TiO2 hybrid exhibits enhanced photocatalytic activity compared with its foundation matrix binary CdS–GR. The improved photocatalytic performance can be attributed to the combined interaction of the longer lifetime of photogenerated electron–hole pairs, faster interfacial charge transfer rate, and larger surface area. In addition, a possible reaction mechanism has been proposed. This work indicates that the careful design of graphene–based composites by coupling graphene to suitable, multiple semiconductors allows the achievement of more efficient photocatalysts, which may have the great potential to improve the capacity for photocatalytic processes significantly. As a proof-of-concept, it is expected that this work could offer new inroads into exploration and utilization of graphene–based nanocomposites as a fertile ground for energy conversion.